Factors Causing Students' Errors in Solving Mathematical Problems Problem Solving Based on the NEA in terms of Gender - Erina Siskawati; Zaenuri Zaenuri; Nur Karomah Dwidayanti; Iwan Junaedi (International Conference on Science, Education, and Technology, 2021)
This study aims to describe the mistakes of students in answering mathematical problem-solving problems. This study used the descriptive qualitative method. This research data is primary and secondary. Data collection techniques are documents, tests, and interviews. The research subjects were 40 students consisting of 10 male upper grade, 10 lower male grade, 10 female upper grade, and 10 lower female grade. The data collection methods were tests and interviews. The results of the study were 1) male students made the most mistakes in the encoding aspect of 199 or 41.29%, 2) female students made the most mistakes in the process skill and encoding aspects of 189 or 28.64%, 3) upper-grade students made the most mistakes in the aspect of process skill and encoding by 175 or 36.31%, 4) lower grade students made the most mistakes in the aspect of encoding by 213 or 32.27%. The conclusion is the factors that cause students' errors in solving problem-solving problems, namely: 1) not being careful in reading the questions, 2) unable to identify what is known from the questions, 3) not memorizing the formula, 4) writing wrong formulas to be used and unable to determine elements, 5) misconception in the counting process and not knowing how to solve it, 6) incorrectly writing the final result of the questions.